KAJIAN RADIKALISME AGAMA DALAM PEMBELAJARAN IPS DI SMP ASSUNAH KOTA CIREBON - Ratna Puspitasari (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2016)
Â AbstractBlack Thursday events of September (11 September 2001) certainly has a lot to change the image of the West against Islam, which is marked by the strengthening of the symptoms of Islamophobia. By placing these events as a context, this paper seeks to put social sciences (social sciences) as a knife analysis to explain the phenomenon of religious radicalism among young people entering the adult early adolescent junior or junior level. This perspective is expected to menemu kaneksplanasi theoretical about the phenomenon of religious radicalism that is rife in some areas in the country. The end goal is that we can minimize the occurrence of cases of radicalism.Key word: radikalisme, stratifikasi sosial, pengetahuan